Tensile strength and dimensional variances in parts manufactured by SLA 3D printing - Tuteski, Ognen; Kochov, Atanas (Scientific-Technical Union of Mechanical Engineering “INDUSTRY 4.0”, 2021)
With the rise of additive manufacturing (AM) technologies, a numerous limitations in conventional manufacturing have been circumvented. Additive manufacturing uses layer-by-layer fabrication of three-dimensional physical models directly from a computer-aided design (CAD) model. The CAD design is transformed into horizontal cross-section layers that are stacked together in physical space until the physical model is completed. This process can be used to directly manufacture tools for injection molding or for any other technology that requires a specific cavity shape to produce a part. This is referred to as Rapid Tooling (RT) and one of the up and coming AM technologies is the resin based stereolithography (SLA).
Keywords: additive manufacturing, 3d printing, tensile strength, stereolithography, SLA